Perspektif Hukum Perdata Internasional terhadap Perkawinan Beda Agama Bagi Warga Negara Indonesia - Insarullah Insarullah; Rahmia Rachman; Erlan Ardiansyah (Universitas Batanghari Jambi, 2022)
The goal of this study is to determine how international private law perceives the legality of interfaith marriages performed by citizens outside of Indonesia in compliance with the Law of Marriage as well as the execution of such marriages. This study employs the normative research methodology, specifically: Academic articles and books with a legal theme, and other sources pertaining to interfaith marriage are used in library research together with primary legal documents such as laws and regulations. Tertiary legal materials are obtained through the internet. The gathered legal materials were then qualitatively examined and given in the form of descriptive and explanatory information. The study's findings demonstrated that because there is a foreign component, interfaith marriage performed by citizens outside of Indonesia is regarded as a part of international private law, specifically because of the domicile, but not in absolute terms because if it violates public order, then foreign elements can be ruled out and it is also regarded as smuggling law because there is the element of intent since it seeks to circumvent the national law, which is then normatively declared invalid and null and void because Indonesian marriage law is based on religious law.